The State, Political Identities and Harry Gwala's Involvement in the Football Struggles in Pietermaritzburg, 1920s-1950s - Dlamuka, Mxolisi (The Journal of Natal and Zulu history, 2019)
This paper traces the relationship between Harry Gwala and the Pietermaritzburg City Council over the provision of football facilities. The roots of this complex and antagonistic relationship can be traced to issues of African urbanisation in the 1920s and how the local state dealt with recreational facilities as a tool of amelioration and social control. A relationship of collegiality and collaboration with the Maritzburg and District Native Football Association developed during the early 1920s, and the City Council became complacent and failed to understand the shifting terrain of the socio-political conditions of the 1940s. In this decade, the Maritzburg and District African Football Association repudiated the City Council's authority and openly aligned itself with the radical political rhetoric of the trade unions and the Communist Party. As Gwala became actively involved in the rejuvenation of the Congress Youth League in Natal, he also became active in the radicalisation of the Football Association; his political stance placed him in a vociferous relationship with City Council officials. Gwala's engagements succeeded in transforming football administration from being an 'arena of entertainment and sociability' to a centre of political consciousness and contestation, and drew on connections with working class struggles in the late 1940s.